A portable electromagnetic head imaging system using metamaterial loaded compact directional 3d antenna - Shahidul Islam M.; Islam M.T.; Hoque A.; Islam M.T.; Amin N.; Chowdhury M.E.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Antenna arrays; Directive antennas; Imaging systems; Metamaterial antennas; Metamaterials; Mobile antennas; Phantoms; Slot antennas; Antenna bandwidth; Antenna performance; Array elements; Free spaces; Frequency ranges; Haemorrhage; Metamaterial (MTM); Parasitic element; Microwave antennas